Game Edukasi Berbasis Android sebagai Media Pembelajaran Matematika untuk Anak Tunarungu - Rizki Yusliana Bakti; Titin Wahyuni; Muhyiddin A M Hayat; Ridwang Ridwang (PROtek : Jurnal Ilmiah Teknik Elektro, 2021)
Education is a right for every individual. Not only those with normal conditions, but also those with special needs such as the deaf. Limited intellectual ability in deaf children has consequences for their difficulties in attending academic lessons including maths lessons. This research aims to create an application as a learning medium to attract deaf children in developing their intelligence. This application was created as a means to provide convenience to deaf children in helping the learning process of mathematics. This study uses observation data collection methods, interviews / questionnaires and library studies. The design method used is the waterfall and the testing technique used is Integration and System testing. The result of this study is an android-based game application named math games. The test results show that this application is easy to learn and there are media that make childrenhappy.